Syeikh Yusuf Almakasari: Karya dan Pemikirannya - Syahrial Syahrial (HISKI, 2007)
Syeikh Yusuf was an ulama who is also known as hero fighting in the struggle for independece. Because of his great service, he was declared a national hero not only by the government of Indonesia but also by South African government. His thoughts regarding tasawuf are reflected in his works. A comprehensive research is needed on this important figure in order is reveal one part the intelectual history of our nation.